2009
DOI: 10.1007/s10764-009-9338-1
|View full text |Cite
|
Sign up to set email alerts
|

Manual Laterality for Simple Reaching and Bimanual Coordinated Task in Naturalistic Housed Pan troglodytes

Abstract: Researchers have shown renewed interest in the study of manual lateralization in chimpanzees. Currently there is no consensus confirming the presence or absence of manual dominance at a species level, mainly for populations in the wild and in semicaptivity. We aimed to evaluate the manual laterality in a group of chimpanzees in an intermediate setting (semicaptivity) via 2 tasks: one simple and unimanual (simple reaching) and the other complex and bimanual (tube task). We replicated the same experiments from H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
2
35
1
Order By: Relevance
“…Unlike spider monkeys, capuchins have been characterized as highly dexterous. In studies of Old World monkeys and chimpanzees that have reported digit use, D2 was also the preferred digit [ Table I; Hopkins, 1995;Llorente et al, 2009Llorente et al, , 2011. By comparison, D2 was preferred in 7 of the 9 spider monkeys in this study (all right-handers and two-thirds of left-handers).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Unlike spider monkeys, capuchins have been characterized as highly dexterous. In studies of Old World monkeys and chimpanzees that have reported digit use, D2 was also the preferred digit [ Table I; Hopkins, 1995;Llorente et al, 2009Llorente et al, , 2011. By comparison, D2 was preferred in 7 of the 9 spider monkeys in this study (all right-handers and two-thirds of left-handers).…”
Section: Discussionmentioning
confidence: 48%
“…The coordinated bimanual TUBE task is an example of a measure that constrains hand use by requiring the subject to Conflicts of interest: None. hold a tube with one hand and extract adhesive food from inside the tube with the opposite hand. First introduced by Hopkins [1995] in chimpanzees (Pan troglodytes), the TUBE task has been widely used in all of the great apes [Bardo et al, 2015;Begg-Reid & Schillaci, 2008;Chapelain et al, 2011;Chapelain & Hogervorst, 2009;Hopkins, 1999a;Hopkins et al, 2001Hopkins et al, , 2003Hopkins et al, , 2011Llorente et al, 2009Llorente et al, , 2011, as well as many monkey species (Table I). Findings from the TUBE task have varied across species, although there is some evidence supporting a pattern of left bias in arboreal species and a right bias in terrestrial species [Meguerditchian et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Hopkins et al (2004) investigated the influences of rearing histories on handedness, while Llorente et al (2009Llorente et al ( , 2011 tested the influence of bimanual and unimanual tasks on handedness. Although no ape study has revealed a manual bias with a similar degree of lateralization compared with the human population, each of the above investigations did return a righthand bias using their own methodological assessment.…”
Section: Introductionmentioning
confidence: 99%
“…These data are provided for comparative purposes, as many studies in the past as well as several more recent studies have analysed pooled data when investigating handedness (e.g. Mosquera et al 2007;Hulme and Matsuzawa 2009;Llorente et al 2009). …”
Section: Introductionmentioning
confidence: 99%